Crucial Role for Basophils in Acquired Protective Immunity to Tick Infestation - Karasuyama, Hajime; Tabakawa, Yuya; Ohta, Takuya; Wada, Takeshi; Yoshikawa, Soichiro (Frontiers in Physiology, 2018)
Ticks are blood-feeding ectoparasites that can transmit various pathogenic organisms to host animals and humans, causing serious infectious diseases such as Lyme disease. Tick feeding induces innate and acquired immune responses in host animals, depending on the combination of different species of animals and ticks. Acquired tick resistance (ATR) can reduce the chance of pathogen transmission from infected ticks to the host. Therefore, the elucidation of cellular and molecular mechanism underlying ATR is important for the development of efficient anti-tick vaccines. In this review article, we briefly overview the history of studies on ATR and summarize recent findings, particularly focusing on the role of basophils in the manifestation of ATR. In several animal species, including cattle, guinea pigs, rabbits and mice, basophil accumulation is observed at the tick re-infestation site, even though the frequency of basophils among cellular infiltrates varies in different animal species, ranging from approximately 3 % in mice to 70 % in guinea pigs. Skin-resident, memory CD4+ T cells contribute to the recruitment of basophils to the tick re-infestation site through production of IL-3 in mice. Depletion of basophils before the tick re-infestation abolishes ATR in guinea pigs infested with Amblyomma americanum and mice infested with Haemaphysalis longicornis, demonstrating the crucial role of basophils in the manifestation of ATR. The activation of basophils via IgE and its receptor FcRI is essential for ATR in mice. Histamine released from activated basophils functions as an important effector molecule in murine ATR, probably through promotion of epidermal hyperplasia that interferes with tick attachment or blood feeding in the skin. Accumulating evidence suggests the following scenario. The 1st tick infestation triggers the production of IgE against tick saliva antigens in the host, and blood-circulating basophils bind such IgE on the cell surface via FcRI. In the 2nd infestation, IgE-armed basophils are recruited to the tick-feeding sites and activated by tick saliva antigens to release of histamine that promotes epidermal hyperplasia, contributing to ATR. Further studies are needed to clarify whether this scenario in mice can be applied to ATR in other animal species and humans.